A five-year review of children with neuroblastoma at Dr. Sardjito General Hospital, Yogyakarta, Indonesia - Sutaryo Sutaryo; Scolastika Dita Kristian (Paediatrica Indonesiana, 2019)
Background Neuroblastoma is the third most common tumor in children, after leukemia and retinoblastoma. The disease presents with a wide range of symptoms. Objective To assess the clinical profiles of children with neuroblastoma at Dr. Sardjito General Hospital from 2012-2016. Methods A retrospective review of all children with neuroblastoma under 18 years of age in the Childrenâ€™s Ward of Dr. Sardjito General Hospital, Yogyakarta from 2012-2016. Patients diagnosed and treated in other hospitals were excluded. Data were taken from the Yogyakarta Pediatric Cancer Registry (YPCR) and medical records. Outcomes were assessed by patient status: alive, died, or lost to follow-up. Results A total of 40 subjects were included in this study. Six (15.0%) patients were diagnosed at <1 year of age, 26 (65.0%) patients at 1 to <5 years of age, 6 (15.0%) patients at 5 to <10 years of age, and 2 (5.0%) patients at â‰¥10 years of age. The male to female ratio was 1.5:1. Four (10.0%) patients had stage IV-S, 34 (85.0 %) patients had stage IV, and 2 (5.0 %) patients had stage II/III of the disease. Proptosis (40.0%) and abdominal mass (35.0%) were the most common chief complaints. Eight (20.0%) patients were alive at the end of observation, 15 (37.5%) died, and 17 (42.5%) were lost to follow-up. The deaths were mostly caused by sepsis. Conclusion Most patients are diagnosed at the age of 1 to <5 years, with a median age of 3 years. Proptosis is the most common chief complaint. Most patients present in stage IV. Overall survival rate is very low. The high numbers of lost to follow-up should be noted.